The Appraisal of Intrusive Images Among Outpatients with Social Anxiety Disorder - Jóhann Pálmar Harðarson 1991- (2016)
Recurrent intrusive images exist across mental disorders, although their specific content varies depending on disorder. However, research on how patients appraise these images has mostly been limited to studies on obsessive-compulsive disorder (OCD). One question concerns whether cognitive behavioral models of OCD are relevant for appraisal processes of intrusive images in other disorders. In this study, it was examined whether patients with social anxiety disorder (SAD) endorse three types of beliefs in relation to intrusive images that have been hypothesized as being specific to OCD (importance of thoughts, responsibility, and control of thoughts). In addition, appraisals of intrusive images in SAD were explored with content analyses. Participants were 35 outpatients (M age = 28.3; SD = 11.5; 54.3% female) at an anxiety treatment center in Iceland diagnosed with SAD (according to the Mini International Neuropsychiatric Interview; MINI), as a primary diagnosis. Participants were interviewed with a semi-structured interview to assess imagery in SAD, which was adapted to focus specifically on appraisals of intrusive images, and ensuing compulsve and other strategies. Sixty percent of the participants reported experiencing clinically significant intrusive images with all of those patients appraising the image as having a negative meaning about themselves. Most SAD patients endorsed beliefs and appraisals of intrusive images that have been hypothesized to be specific to OCD. However, content analysis revealed that the most significant appraisals seemed specific to SAD, such as beliefs of having a flawed or a weak self, and believing others to be critical or cruel. There appear to be greater similarities between appraisal processes in SAD and OCD than previously believed. Future directions and treatment implications are discussed. Keywords: Appraisals, intrusive images, obsessive-compulsive disorder, social anxiety disorder.